Efficient and Low-Cost Removal of Methylene Blue using Activated Natural Kaolinite Material - Christyowati Primi Sagita; Limpat Nulandaya; Yehezkiel Steven Kurniawan (Journal of Multidisciplinary Applied Natural Science, 2021)
Clays are low-price and very useful material for water treatment purpose. In this work, we reported the application of activated natural kaolinite material which obtained from Wediombo beach, Yogyakarta for methylene blue adsorption. The natural kaolinite material was activated under an acidic condition to obtain the activated kaolinite material. The activated kaolinite material was characterized using Fourier transform infrared, X-ray diffraction, scanning electron microscope, and surface analysis. From the adsorption experiment, the activated kaolinite material gave moderate adsorption percentages for methylene blue. The adsorption kinetics followed the Ho and McKay kinetic model while the adsorption isotherm followed Langmuir model. The qmax value for methylene blue adsorption using activated natural kaolinite material was at a moderate level (3.40 mg g-1). The plausible adsorption mechanism of methylene blue on the surface of activated kaolinite material happened through hydrogen bondings and/or electrostatic interactions. These findings are important for a wastewater treatment using a low-cost adsorbent material.